Simulation of the normal and emergency operation of interconnected power system of Ukraine for frequency stability study - Kyrylenko, O.V.; Pavlovsky, V.V.; Steliuk, А.О.; Lenga, O.V.; Vyshnevskyi, M.V. (Технічна електродинаміка, 2017)
Integration of interconnected power system (IPS) of Ukraine to the European Network Transmission System Operators for Electricity (ENTSO-E) requires an improvement of Ukrainian frequency automatic emergency control and harmonization with load-frequency control according to requirements of ENTSO-E. In order to investigate processes of frequency and active power control, it is necessary to develop the detailed simulation model including models of automatic under frequency load shedding (UFLS) relays, special protection automatics (SPA) of the nuclear power plants, automatic generation control (AGC) as well as 750-220 kV transmission networks of IPS of Ukraine. The frequency stability phenomena have been studied by time domain simulation using the detailed model realized in DIgSILENT PowerFactory software. The simulation results for different disturbances are presented.